2001
DOI: 10.1097/00005176-200103000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m HMPAO-Labeled Leukocyte Imaging Compared with Endoscopy, Ultrasonography, and Contrast Radiology in Children with Inflammatory Bowel Disease

Abstract: Leukocyte-labeled scintigraphy, a noninvasive and reproducible technique, is a useful tool in the diagnosis and therapeutic strategy of IBD, and provides information on the presence, the intensity, and the extent of the disease, particularly in the terminal ileum. Leukocyte-labeled scintigraphy may not replace colonoscopy with biopsies for diagnosis confirmation. Its reliability seems higher than that of ultrasonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 42 publications
1
21
1
2
Order By: Relevance
“…However, when results were separately calculated for the Crohn's Disease patients, the specificity was lower, 63%. The specificity is lower than previously reported 11,[42][43][44] and probably reflects the small number of patients without macroscopic findings in our cohort, implying a selection bias. Since this is the first study of leukocyte scintigraphy compared with complete endoscopic evaluation of the small bowel, our results should be considered more reliable than studies using indirect methods to demonstrate inflammation.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…However, when results were separately calculated for the Crohn's Disease patients, the specificity was lower, 63%. The specificity is lower than previously reported 11,[42][43][44] and probably reflects the small number of patients without macroscopic findings in our cohort, implying a selection bias. Since this is the first study of leukocyte scintigraphy compared with complete endoscopic evaluation of the small bowel, our results should be considered more reliable than studies using indirect methods to demonstrate inflammation.…”
Section: Discussioncontrasting
confidence: 93%
“…43,45 Several studies in children have shown results comparable to those in adults. 10,11,46 A more widespread use of leukocyte scanning can be advocated inasmuch as the method is noninvasive, without the need for bowel preparation, and, in comparison to other explorations, preferred by patients. 6 Capsule endoscopy is an emerging technique for the detection of small bowel Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent these disadvantages due to the nonspecific nature of 18 F-FDG uptake in the bowel, other scintigraphic techniques that target immune cells have previously been tested for imaging IBD, including polyclonal immunoglobulins and monoclonal antibodies against granulocytes and adhesion molecules (7,8,(26)(27)(28). Also 67 Ga-citrate uptake has been shown to correlate with the extent and activity of disease in both Crohn disease and ulcerative colitis (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…En cualquier caso, en estos estudios se establece que la ecografía se muestra muy sensible y especí-fica en la detección de las lesiones de colitis ulcerosa. Las cifras de precisión global se encuentran entre el 63 y el 95% (21,(26)(27)(28)(29)(30)(31)(32)(33). Esta gran variabilidad en los resultados se explica en los diferentes patrones oro empleados en estos estudios para evaluar la precisión de la ecografía (endoscopia o técnicas radiológicas), la heterogeneidad de los pacientes seleccionados y las notables diferencias en los tamaños muestrales.…”
Section: Discussionunclassified